Knowledge and attitudes of undergraduate medical students in Kenya towards solid organ donation and transplantation: Are Africa’s future clinicians prepared? - Mpekethu, Nelson Mweteri; Mongare, Newnex Brian; Mutua, Victor; Wangari, Marie-Claire; Csefalvay, Chris von; Ojuka, Daniel (African Journal of Nephrology, 2021)
Background: Solid organ donation and transplantation remains grossly underdeveloped in most African countries. The knowledge and attitude of tomorrow’s professionals may be key to the improvement of these services. Methods: A sample of undergraduate medical students from all the medical schools in Kenya offering Bachelor of Medicine and Bachelor of Surgery degrees were surveyed using a self-administered, web-based questionnaire, between July and September 2018. Results: Of the 303 participants, 167 (55.1%) were female. Only 8.9% of the students had read the laws governing transplantation in Kenya. An even lower percentage (3.3%) felt that they had learned enough about solid organ donation and transplantation from their medical curriculum. More than half (53%) of the respondents would subscribe as solid organ donors, which reduced to 47% when it came to consenting to donating their relatives’ organs. Less than half of the students (40%) considered they would be comfortable introducing the topic or confident answering questions (23%) related to organ donation and transplantation. Only 9.9% of the sample had ever spoken to a patient about organ donation. There was no significant association between level of study (preclinical versus clinical) and comfort introducing the topic of organ donation (P = 0.206) or experience talking to a patient about the subject (P = 0.102). Conclusion: Undergraduate medical students have significant knowledge gaps regarding organ donation and transplantation and feel ill-prepared to approach a potential donor or transplant recipient.